Pengaruh pemlastis nabati terhadap sifat elastomer termoplastik berbasis campuran karet alam/poli propilena - Nurhajati, Dwi Wahini; Supraptiningsih, Supraptiningsih; Sarengat, Nursamsi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2015)
Vegetable plasticizer is a plasticizer that is derived from renewable raw materials, that are used as an alternative to petroleum-based plasticizer. The purpose of this research was to compare the effect of the vegetable and plasticizer with petroleum plasticizers on the mechanical properties of (Thermoplastic Elastomer) TPE. Vegetable plasticizer used in this study is a modified castor oil. Natural rubber/polypropylene (KA/PP) based TPE was made in an internal mixer at a temperature of 180ºC with a variousvarious ratio KA/PP ratio and type of plasticizer. In general, modified castor oil as a plasticizer has a more positive effect on the mechanical properties of TPE in various ratios of KA/PP, is mainly related to improvement of properties of tensile strength, elongation at break and flexing resistance 100 kcs. The best formula of TPE is a TPE that is composed of KA/PP 60/40 using modified castor oil. XRD results showed that TPE is dominated by amorphous phase.Keywords: castor oil, natural rubber, polypropylene, TPE.ABSTRAK Pemlastis nabati merupakan pemlastis yang berasal dari bahan baku yang terbarukan yang digunakan sebagai alternatif untuk pemlastis berbasis minyak bumi. Tujuan penelitian ini untuk membandingkan pengaruh pemlastis nabati dengan pemlastis dari minyak bumi terhadap sifat mekanik elastomer termoplastik. Pemlastis nabati yang digunakan dalam penelitian ini adalah minyak jarak yang telah dimodifikasi. TPE berbasis campuran kompon karet alam (KA)/poli propilena (PP) dibuat di dalam internal mikser pada suhu 180°C dengan variasi perbandingan KA/PP dan jenis pemlastis. Secara umum minyak jarak termodifikasi sebagai pemlastis mempunyai pengaruh yang lebih positif terhadap sifat fisis TPE pada berbagai rasio KA/PP terutama terkait perbaikan sifat kuat tarik, perpanjangan putus dan ketahanan retak lentur. Formula TPE terbaik adalah TPE yang dikomposisi dari KA/PP pada rasio KA/PP 60/40 menggunakan pemlastis minyak jarak. Hasil XRD memperlihatkan bahwa TPE hasil penelitian didominasi fasa amorf. Kata kunci: karet alam, minyak jarak, poli propilena, TPE